Not Eight, But Four: Muhammad Syahrūr’s Reconstruction of Mustaḥiq Zakah’s Classification - Muhammad Misbahul Munir; Khamim Khamim (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This article analyzes Muhammad Syahrūr’s thoughts on the mustaḥiq zakah (zakat recipient) classification based on his interpretation of Qur’anic verse, QS. al-Taubah [9]: 60. Syahrūr’s perspective is unique because it challenges the classification of mustaḥiq zakah that Islamic jurists have widely accepted. The article uses a literature review with a Gadamer hermeneutic approach. Data was collected through text studies and analyzed using descriptive-analytical techniques. The study found that Syahrūr classified mustaḥiq zakah into four categories: fakīr (poor person), miskīn (needy person), ghārim (the debtor), and ibn sabīl (wayfarer). Using a scientific-historical approach, Syahrūr expanded the meaning of fakīr to include orphans, miskīn to include people with special needs, ghārim to include debts for paying diyah (blood money) for wrongful killing (al-qatl al-khaṭa’), and ibn sabīl, which refers to travelers. Syahrūr’s interpretation of QS. al-Taubah [9]: 60 is a product of his scientific-historical approach, which he developed while in Moscow under the influence of the prevailing logic of the time (episteme), the structuralism of Russian formalism, and his linguistic teacher, Ja’far Dak al-Bāb. Syahrūr’s approach required him to observe the contemporary object’s condition in understanding QS. al-Taubah [9]: 60. The poor conditions in Syria, both internal and external factors, influenced Syahrūr’s interpretation of QS. al-Taubah [9]: 60.